Proximate, Protein, and Fat Analysis of Striped Catfish (Pangasianodon Hypopthalmus) - Agung Ary Wibowo; Triawanti Triawanti; Nathania Hosea; Nathan Aditya Willyanto (Journal of Wetlands Environmental Management, 2023)
Striped catfish is one of the most popular types of freshwater fish consumed by Indonesians. Striped catfish contains Monounsaturated Fatty Acids (MUFA) and Polyunsaturated Fatty Acids (PUFA). MUFA in striped catfish (Omega-3, Omega-6, and Omega-9 Fatty Acids) plays an important role in fat transport and metabolism, immune system regulation, and maintaining cell membrane function and integrity. This study emphasizes the comparison of wild and cultivated striped catfish. This study is a descriptive study to compare and determine the analysis result of proximate, protein, and fat between cultivated and wild striped catfish, and compare the analysis of this study with other studies. Analysis of proximate and protein content data was carried out using the Independent T-Test parametric test, while the fat content data analysis was carried out using the Mann-Whitney parametric test. There was a significant difference in the proximal and fat levels of cultivated and wild striped catfish with α=0.021 (α<0.05), and there was no significant difference in protein content with α=0.021 (α<0.05). The results of comparison with other studies showed that the proximate, protein, and fat of striped catfish in this study were higher than in other studies. This study showed that cultivated striped catfish has a better result analysis of proximate, fat, and protein content than wild catfish. Striped catfish have a high protein and fat content, high adaptability, and is easy to cultivate as compared to the wild ones. Therefore, striped catfish have the potential to be an alternative for nutrition improvement, and the cultivation of striped catfish may reduce the damage to wetland ecosystems.